Integrated approach to model distribution and assess habitat suitability of killifish species in Oman’s local streams (wadis) under current and future climate conditions - Aziza S. Al Adhoobi; Amna Al Ruheili; Saud M. Al Jufaili; Wenresti Gallardo (PLoS ONE, 2026)
Freshwater ecosystems in arid regions possess extraordinary levels of biodiversity, yet they are subject to unprecedented pressures of climate change and anthropogenic activities. We employed an integrated approach of incorporating species distribution modeling (MaxEnt), habitat suitability modeling, and protected area analysis to assess conservation requirements for two endemic/native killifish ( Aphaniops kruppi and A. stoliczkanus ) in Oman’s freshwater ecosystems. Using MaxEnt with CHELSA bioclimatic variables and topographic indices, we modelled climate change impacts under three shared socio-economic pathways (SSP1–2.6, SSP3–7.0, and SSP5–8.5) spanning 2011–2100. Predictive models demonstrated remarkable accuracy (AUC: 0.974 for A. kruppi , 0.950 for A. stoliczkanus ) revealing unique biogeographical patterns. A. kruppi showed restricted southern distribution dependent on monsoon moisture levels, with mean monthly climate moisture index (Cmi_m; 39.9%), mean diurnal range (Bio2; 18.3%), and sediment transport index (STI; 8.4%) as key variables. The distribution of A. stoliczkanus exhibited a more expansive northern range influenced by winter precipitation patterns, with precipitation of the coldest quarter (Bio19; 31%), the sediment transport index (STI; 20.2%), and the stream power index (SPI; 13.3%) as key drivers. Climate projections revealed high extrapolation risk (85–95%) with anticipated habitat reductions. Habitat suitability assessment of 12 stream sites (Boyce Index: 0.894) revealed unexpected specialization-dominance trade-off, where optimal Aphaniops conditions led to competitive exclusion, resulting in negative correlations between habitat suitability and aquatic biodiversity (Shannon diversity: r = −0.577, p = 0.049). Dissolved oxygen emerged as most critical parameter (mean suitability: 0.771 ± 0.308), with only 25% of sites demonstrating a Highly Suitable status. Spatial analysis revealed significant protection gaps: only 0.31–1.34% of high-suitability habitats and 2.6% of high-density wadis currently protected, requiring 6–24-fold increases to meet conservation targets. Species hybridization necessitates landscape-level conservation maintaining connectivity for gene flow. Results demonstrate that desert aquatic fauna conservation requires integrated strategies addressing climate dependencies, multi-habitat corridor protection, tiered water quality standards, and adaptive management accounting for hybridization zones, providing a replicable model for conservation in water-limited environments.